Green Building Index (GBI) certification for Damansara - Shah Alam elevated expressway’s toll plazas / Muhammad Lukman Hakim Ahmad Shahrul Nizam - Ahmad Shahrul Nizam, Muhmammad Lukman Hakim (Universiti Teknologi MARA, Perak, 2022)
Energy has become one of the most vital and significant aspects of a country's growth; nations with a large proportion of energy and resources are seen as powerful; currently, a country's energy and resources are a major indicator of its strength and progress. Economic development has become increasingly important in today's globe, as natural resources are becoming increasingly scarce, and available housing space is shrinking as the world's population grows. As a result, there is a greater demand for green building construction to ensure sustainable growth and minimize resource consumption. Green building is the process of constructing buildings and employing techniques that are environmentally friendly and resource efficient throughout a building's life cycle, from design to construction, operation, care, renovation, and deconstruction. Although some world-class green buildings have been constructed in Malaysia in recent years, the concept of green buildings for the general public is still in its infancy.